PENGARUH PENGETAHUAN IBU TERHADAP PERAWATAN TALI PUSAT PADA BBL DI PUSKESMAS TANAH ABANG JAKARTA PUSAT PERIODE 2021 - Larasati, Manggiasih Dwiayu; Rahmani, Salwa Fadhilah; Haqqi, Putri Mashiral; Ananda, Zenea Nurmahlia (Universitas Tribhuwana Tunggadewi, 2021)
Tetanus neonatorum and umbilical cord infection are the causes of morbidity and mortality continuously in various countries. The umbilical cord of a newborn is a very sensitive part and the most susceptible to bacterial colonization. Therefore, it requires maternal knowledge about how to properly care for the umbilical cord. This study aims to analyze the effect of maternal knowledge on umbilical cord care in newborns at Tanah Abang Public Health Center 2021. This study is a descriptive analytic study using a cross sectional approach. The population of this study was 75 mothers who made neonatal visits in January 2021. Sampling using purposive sampling obtained 36 mothers. The results showed that there were 23 respondents (63.9%) who performed maintenance on the umbilical cord according to the procedure while 17 respondents (47.2%) had good knowledge. Based on statistical test, the p value was 0.023 0.05, so it could be concluded that maternal knowledge influenced the proper care of the umbilical cord.